Framing cyber warfare: an analyst's perspective. (July 2019) - Ween, Anthony; Dortmans, Peter; Thakur, Nitin; Rowe, Cayt
Understanding how new phenomenon impacts complex systems requires the capacity to examine and characterize how the system might respond. A soft-systems approach to analyzing cyber warfare can be flexible enough to deal with the inherent complexity and rates of change and still support a more rigorous representation. This paper presents high-level models that use distinct lenses to provide an understanding of cyber implications in the system. These reference models are intended to allow a consistent approach to be applied across conventional and cyber warfare domains and provide a common language to underpin debate and discussion.